University students' perceptions of ELF in mainland China and Taiwan. (February 2016) - Ren, Wei; Chen, Yuan-shan; Lin, Chih-Ying
Abstract: This study examined mainland Chinese and Taiwanese students' perceptions of two aspects of English as a Lingua Franca (ELF): phonology and lexico-grammar. The researchers surveyed a total of 400 students at two universities in mainland China and at two universities in Taiwan (200 in each area). The results indicated that although students in both groups were aware that they could not speak English as native speakers did, they still preferred to achieve a native speaker accent. They admitted that they spoke with Chinese accents, but they believed that their accents were intelligible and acceptable. Nevertheless, the students in both groups tended to not maintain their local accents in English. With respect to ELF lexico-grammar, both groups considered some features incorrect, but they were uncertain about others. However, they could understand and tended to accept all the ELF sentences. The present study also revealed variations between the two groups with respect to their perceptions of ELF phonology and lexico-grammar. Given that little research has compared ELF users' perceptions across different geographical areas, this study addresses an important research gap by investigating the interaction of ELF perceptions and local contexts. Findings of the study may have important implications for ELF researchers and practitioners. Highlights: We examined Mainland Chinese and Taiwan Chinese learners' perceptions of ELF. Both Mainland Chinese and Taiwan Chinese learners preferred to achieve a native speaker accent. ELF lexico-grammar features posed different difficulties to learners in Mainland China and Taiwan. Mainland Chinese and Taiwan learners could understand and tended to accept all the ELF sentences.